2017
DOI: 10.2147/ppa.s139851
|View full text |Cite
|
Sign up to set email alerts
|

Treatment adherence in hemophilia

Abstract: Prophylactic clotting-factor regimens reduce the occurrence of bleeding episodes and maintain joint health in individuals with moderate and severe hemophilia. However, these outcomes are only achieved with adherence to prescribed prophylaxis regimens. There are several types of barriers to adherence related to key patient, condition, treatment, health-care system, and/or socioeconomic variables. Notably, health-care professionals may not prescribe prophylaxis if they perceive that a patient will be nonadherent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
181
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(185 citation statements)
references
References 73 publications
1
181
0
3
Order By: Relevance
“…Patients with severe haemophilia who do not receive prophylaxis usually have 30‐35 joint bleedings a year, and they are at high risk of developing severe arthropathy. With increasing severity and number of affected joints, BMD significantly decreases . In our study, thirty five patients (70%) were on low‐dose prophylactic factor VIII therapy with a dose of 15 U/kg twice weekly.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with severe haemophilia who do not receive prophylaxis usually have 30‐35 joint bleedings a year, and they are at high risk of developing severe arthropathy. With increasing severity and number of affected joints, BMD significantly decreases . In our study, thirty five patients (70%) were on low‐dose prophylactic factor VIII therapy with a dose of 15 U/kg twice weekly.…”
Section: Discussionmentioning
confidence: 99%
“…9 Our results, based on the perspectives of patients, suggest that visualization techniques could be a helpful patient-centred care strategy. 17,18 In another study, 19 Several decision aids have been developed for haemophilia. A previous qualitative study demonstrated that a better understanding determines the ability to practice prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a good relationship between care providers and PWH has been found to be associated with treatment adherence in haemophilia 17,18. This resulted in increased patient quality of life (QoL) and enhanced illness perception and stabilization of joint health after 1 year.…”
mentioning
confidence: 99%
“…Among the barriers to achieving optimal outcomes is adherence to the FVIII dosing regimen which mandates frequent, intravenous injections of concentrates of FVIII and achieving circulating FVIII levels sufficient to prevent bleeding including with physical activity …”
Section: Introductionmentioning
confidence: 99%